Factors Affecting Consumer Purchasing Decisions on Healthy Catering - Rizkitania, Annisa; Auliyah, Aidah; Wani, Yudi Arimba (Media Gizi Indonesia, 2022)
The higher public awareness of healthy food the more increase of the existence of healthy catering which makes the healthy catering business more competitive. The objective of this research to find out what factors influence consumer purchasing decisions in healthy catering and its relation to the impact of Covid-19. This study uses a literature review method by selecting studies that refer to the Preferred Reporting Items for Systematic Review and Meta-Analyses Statement and selected quantitative studies. For the final result, 23 studies were included. There are factors that influence purchasing decisions on consumers, both internally and externally. Internal factors include gender, social economic history, knowledge, and the trust factor for a product. For external factors like price, product quality, product marketing, product attributes, cultural background, quality service, and the health effect. During Covid-19 pandemic, there have been changes in the factors that influence consumer purchasing decisions. Respondents stated that they prefer to adopt healthy eating behavior, but in other countries is difficult to find fresh products, so they tend to buy frozen and canned food.